2012
DOI: 10.1111/are.12004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density and body physical contact on growth of sea cucumber,Apostichopus japonicus

Abstract: The present study was conducted to investigate the effects of physical contact on the growth of Apostichopus japonicus through various stocking densities, group culture and physical isolation culture. The results showed that the specific growth rates (SGR), the feed conversion efficiencies and the energy used for growth of the animal decreased with the increase in stocking density, while the coefficient of variations (CV) in group culture treatments increased. In high density treatments (4, 6 ind./40 L), the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 31 publications
(48 reference statements)
4
27
0
Order By: Relevance
“…FCE of the juvenile sea cucumber fed Sargassum thunbergii diet showed the highest value at 16°C (An et al., ) which is similar to the present experiment. Higher FCE value was recorded using the dry pellets for juvenile sea cucumber two individuals in a tank, and the FCE value decreased with increasing the density (Pei et al., ). The nutritional composition, taste and palatability of feed ingredients can influence feed intake and feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FCE of the juvenile sea cucumber fed Sargassum thunbergii diet showed the highest value at 16°C (An et al., ) which is similar to the present experiment. Higher FCE value was recorded using the dry pellets for juvenile sea cucumber two individuals in a tank, and the FCE value decreased with increasing the density (Pei et al., ). The nutritional composition, taste and palatability of feed ingredients can influence feed intake and feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the dietary requirements is important for commercial aquaculture. Studies have examined the nutritional requirements (Choi, Seo & Lee, ; Okorie et al., , ; Seo & Lee, ), feed ingredients (Liu, Dong, Tian, Wang & Gao, ; Seo, Shin & Lee, ,b; Shi, Dong, Wang, Gao & Tian, ; Shi et al., ; Slater, Jeffs & Carton, ; Yuan et al., ), diet formation (Xia et al., 2013), culture technology (Pei, Dong, Wang, Gao & Tian, ; Sui, ), water quality (An, Dong & Dong, ; Xie, Zhao & Yang, ; Yuan, Yang, Wang, Zhou & Gabr, ) of sea cucumber. Plant‐based ingredients, especially macroalgae, such as brown alga Sargassum thunbergii (Mertens ex Roth), are considered as a necessary part of the diet of A. japonicus (Xia et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al reported that individual growth variation of sea cucumber increased with the increase of stocking densities, whereas no significant differences in variation were found when the density was over 30 inds [5]. Pei et al gave a similar result, which showed that physical contact caused by stocking density could affect the individual growth variation of sea cucumber [6]. However, the genetic factor was thought to be more effective than stocking density [6].…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al gave a similar result, which showed that physical contact caused by stocking density could affect the individual growth variation of sea cucumber [6]. However, the genetic factor was thought to be more effective than stocking density [6]. Liang et al reared sea cucumber individually to eliminate possible effects of environmental differentiation, such as social interaction, stocking density, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the factors that affect growth and survival of juveniles is important in optimizing a culture production system. Stocking density is one of the most critical factors affecting the growth of many cultured marine organisms (Battaglene, Seymour & Ramofafia, ; Daly, Swingle & Eckert, ; Dong et al., ; Nga et al., ; Pei, Dong, Wang, Gao & Tian, ; Zhang et al., ). High stocking density affects growth directly through increased competition for food and space and indirectly through degradation of water quality (Huchette, Koh & Day, ; Nga et al., ).…”
Section: Introductionmentioning
confidence: 99%